2021
DOI: 10.1109/lmwc.2021.3050765
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Peak Power Handling in Microstrip Bandpass Filters by Using Rounded-End Resonators

Abstract: This work describes a new strategy for improving the peak power handling capability (PPHC) of microstrip bandpass filters (BPFs) without any degradation in the electrical performance. For this purpose, a new resonator topology with rounded open-circuit terminations is proposed. Using this strategy, sharp edges are avoided and a reduction of the maximum peak voltage (V peak ) is obtained, leading to higher peak power thresholds. An in-depth analysis of the variation of V peak and PPHC as a function of the circl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 16 publications
(17 reference statements)
0
4
0
Order By: Relevance
“…1(b), where, as it can be seen, the cavity is also located on the top plate. However, the four central pins of the bottom metal plate are replaced by a unique metal block, in which the corners have also been rounded with a radius r in order to avoid the sharp edges, where high electric fields can appear (see [12], [24]). By making this change, the TE 101 -like mode can still be excited, and the maximum electric field can be reduced and shifted to the center of the cavity, as shown in Fig.…”
Section: Analysis Of the Modified Resonant Structurementioning
confidence: 99%
See 1 more Smart Citation
“…1(b), where, as it can be seen, the cavity is also located on the top plate. However, the four central pins of the bottom metal plate are replaced by a unique metal block, in which the corners have also been rounded with a radius r in order to avoid the sharp edges, where high electric fields can appear (see [12], [24]). By making this change, the TE 101 -like mode can still be excited, and the maximum electric field can be reduced and shifted to the center of the cavity, as shown in Fig.…”
Section: Analysis Of the Modified Resonant Structurementioning
confidence: 99%
“…The two filters have been measured at 22 • C in a pressured controlled chamber from 2 to 1013 mbar in order to obtain their respective Paschen curves. Different detection methods have been used to identify the corona discharge, as detailed in [10]- [12], where similar measurement campaigns were carried out for microstrip BPFs.…”
Section: In Purplementioning
confidence: 99%
“…Like another power handling problem, multipactor, one of the most important aspects of corona research is how to suppress corona effect. Due to the similarity between multipactor and corona, they sometimes can be suppressed by using similar techniques such as electrical structure design/optimization [11,12], dielectric filling [13,14] as well as surface treatments [15]. For example, measurement results in [11] show that by introducing rounded-end resonators, hairpin microstrip bandpass filter's corona threshold can be improved by 2.1 dB.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the importance of studying the peak power limits that microwave devices can withstand, some works have focused their efforts on studying the gas breakdown in RWs [35], [36], [37]. Some other contributions have analyzed this same physical effect in planar devices [6], [38] and several design solutions have been proposed to enhance the PPHC [39], [40], [41]. With respect to previous research related to the corona discharge breakdown thresholds in GW technology, a preliminary study based on simulations for guided structures can be found in [42], where measured results are not presented.…”
Section: Introductionmentioning
confidence: 99%